1997
DOI: 10.1046/j.1365-2265.1997.2851090.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐GAD65 autoantibody in Taiwanese patients with insulin‐dependent diabetes mellitus: effect of HLA on anti‐GAD65 positivity and clinical characteristics

Abstract: Prevalence of GAD65 autoantibody among Taiwanese subjects with IDDM was negatively correlated with duration of disease. Different determinants in the HLA-DR locus contributed to the clinical onset of IDDM but not to GAD autoimmunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…Interestingly, studies that consider <2 or <5 years of disease in the recent diagnosis category have demonstrated a relatively lower prevalence of the antibody in these groups (54.9-56%), closer to our results (25,26). Nevertheless, not all investigators have shown remarkable differences between individuals with recent and long-standing disease.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Interestingly, studies that consider <2 or <5 years of disease in the recent diagnosis category have demonstrated a relatively lower prevalence of the antibody in these groups (54.9-56%), closer to our results (25,26). Nevertheless, not all investigators have shown remarkable differences between individuals with recent and long-standing disease.…”
Section: Discussionsupporting
confidence: 87%
“…Even though the drop of prevalence in the first year of the disease is a possible explanation, most previous studies have reported a higher frequency of GADA in patients with T1D with a shorter duration of the disease regardless of whether this category comprised only individuals diagnosed for less than 1 year (5,12) or included patients with the duration of disease up to five years (25,26). Interestingly, studies that consider <2 or <5 years of disease in the recent diagnosis category have demonstrated a relatively lower prevalence of the antibody in these groups (54.9-56%), closer to our results (25,26).…”
Section: Discussionmentioning
confidence: 98%
“…The presence of anti-GAD antibodies was tested in 217 samples from the type 1 diabetic patients with an immunoprecipitation method (21). Briefly, in vitro transcription of a plasmid DNA containing human GAD 65 sequences (provided by Dr Dyrberg at Novo Nordisk A/S Industry, Denmark) and translation with [ 35 S]meth-ionine labeling was performed according to the manufacturer's instructions (TNT TM T7 Coupled Reticulocyte Lysate System, Promega, Madison, WI, USA).…”
Section: Antibodies To Glutamate Decarboxylase (Anti-gad)mentioning
confidence: 99%
“…reported GAD65 more frequent in females than males. 30,33,35 Concerning the association between GAD65Ab and HLA alleles, this study showed a link between presence of GAD65Ab and HLA-DR3, HLA-DQA1*05:01. This relation with HLA-DR3 sustained the observations of Serjeant son and coworkers.…”
Section: Discussionmentioning
confidence: 59%
“…Our results, although no consistent with some studies, support the viewpoint that the GAD65Ab, declines slowly and persists in the blood for years. [30][31][32][33][34] Study results showed also no link between GAD65 prevalence and gender. These results were like those of Chuang and co-workers and Chan and co-workers whereas Thai and al.…”
Section: Discussionmentioning
confidence: 99%